197k views
1 vote
Drag the tiles to the boxes to form correct pairs. Simplify each expression, and then make changes the equivalent expressions.

Drag the tiles to the boxes to form correct pairs. Simplify each expression, and then-example-1

2 Answers

6 votes

4(2x^2+3y^2)^2 = 16x^4 + 48x^2y^2 + 36y^4

(4x-5)(16x^2 + 20x + 25) = 64x^3 - 125

4 ( 2x^2 + 3y^2)(2x^2 - 3y^2) = 16x^4 -36y^4

hope that helps

User Orrymr
by
4.5k points
0 votes

Answer :


64x^3-125
(4x-5)(16x^2+20x+25)


4(2x^2+3y^2)^2
16x^4+36y^4+48x^2y^2


4(2x^2+3y^2)(2x^2-3y^2)
16x^4-36y^4

Step-by-step explanation :

(a) The given expression is:


64x^3-125


=(4x)^3-(5)^3

Using identity :
a^3-b^3=(a-b)(a^2+2ab+b^2)


=(4x-5)(16x^2+20x+25)

(b) The given expression is:


4(2x^2+3y^2)^2

Using identity :
(a+b)^2=a^2+2ab+b^2


=4[(2x^2)^2+(3y^2)^2+2(2x^2)(3y^2)]


=4[4x^4+9y^4+12x^2y^2]


=16x^4+36y^4+48x^2y^2

(c) The given expression is:


4(2x^2+3y^2)(2x^2-3y^2)

Using identity :
(a+b)(a-b)=a^2-b^2


=4[(2x^2)^2-(3y^2)^2]


=4[4x^4-9y^4]


=16x^4-36y^4

User Nick Kavadias
by
4.7k points